Continuity and inversion of the wavelet transform - Pathak, R.S. (Integral transforms and special functions, 1998)
Using a converse form of the Schwarz inequality L 2 -continuity results for the wavelet transform and its adjoint are obtained. A relation between the wavelet transform and the Fourier transform is established. The self-adjoint case is investigated and a complex inversion formula for the wavelet transform is derived. Wavelet transform of generalised functions is investigated.